FRIENDLY ISLAMIC PREACHING THROUGH LITERARY WORKS: STUDY OF LUKISAN KALIGRAFI SHORT STORY COLLECTION BY A. MUSTOFA BISRI - Abdul Karim Wirawan; Khumaidi Abdillah (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
This paper dedicated to examine and explore the model of dakwah found in the collection of short stories Lukisan Kaligrafi by A. Mustofa Bisri. The dakwah model examined in this paper is a friendly Islamic dakwah model. Friendly Islam is the face of Islam that is full of politeness and tolerance, not the face of Islam which is hard and full of anger. The collection of short stories Lukisan Kaligrafi is suitable as a medium to preach this friendly Islam because the short stories in this collection of short stories tell the twists and turns of the Islamic religious life experienced by the characters in each of the short stories. Therefore, this paper will try to identify (1) the proselytizing politeness in a collection of short stories Lukisan Kaligrafi and (2) the portrait of religious tolerance in a collection of short stories Lukisan Kaligrafi. Accentuating the friendly face of Islam is important because today the face of Islam is heavily tarnished by the actions of some groups acting in the name of Islam by acting outside the meaning of Islam which is rahmatan lil ‘ālamīn